Utilization of Kersen Leaf Extract (Muntingia calabura L.) in Non Aerosol Foot Spray Preparation as Antibacterial Against Staphylococcus epidermidis - Nadhifa Ainun Syafira; Prisca Deviani Pakan (Cendana Medical Journal, 2025)
Introduction: The condition of the feet that are often covered by socks and shoes causes the feet to become sweaty and moist. If the sweat is mixed with the bacteria that are involved in the degradation process, it will cause an odor. Preventing foot odor requires a convenient antibacterial product such as foot spray. However, many foot spray products contain high levels of alcohol, which can cause skin irritation. Therefore, the implementation of natural antibacterial ingredients needs to be incorporated to reduce its use, such as kersen leaves (Muntingia calabura L.). Objectives: Knowing and analyzing foot spray preparations and their benefits as antibacterial against Staphylococcus epidermidis. Method: This research is a true experimental design with a post-test only control group. The study involved five treatment groups: kersen leaf extract foot spray at concentrations of 1%, 5%, and 10%; a positive control group consisting of commercial foot spray (Guardian); and a negative control group which utilized foot spray base with S. epidermidis as the test bacteria. The method of antibacterial testing uses the disc diffusion method. The results were analyzed using the One-Way Anova statistical test. Result: The kersen leaf extract foot spray preparation was tested for its ability to inhibit the growth of S. epidermidis. Results showed that the inhibition zone diameter at 1% concentration was moderate (7.82 mm), while at 5% concentration it remained moderate (8.62 mm), and at 10% concentration it classified as strong (10.28 mm). The analysis results found significant differences between treatment groups with a significance value of p < 0.05. Conclusion: Kersen leaf extract (Muntingia calabura L.) foot spray preparation has antibacterial activity against Staphylococcus epidermidis and all formulations have optimal physical characteristics. Keywords: Kersen Leaf Extract; Muntingia calabura L.; Foot Spray; Antibacterial; Staphylococcus epidermidis